Suboptimal child healthcare practices and the development of multiple infectious diseases in children aged 24–59 months - Sulistiyowati, Ning; Tjandrarini, Dwi Hapsari; Titaley, Christiana Rialine; Que, Bertha J.; Hidayangsih, Puti Sari; Suparmi,; Sudikno, Sudikno; Purwatiningsih, Yuni; Indrawati, Lely; Siahaan, Selma; Adyarani, Windy Pradita (Frontiers in Public Health, 2024)
Background Infections continue to be a major cause of death among children under the age of five worldwide. This study aimed to identify the factors associated with the development of multiple infectious diseases in children aged 24–59 months in Indonesia. Methods Data from the 2018 Basic Health Research conducted by the Ministry of Health, Republic of Indonesia, were used. Information from 39,948 children aged 24–59 months was analyzed. The outcome variable was the development of multiple infectious diseases, that is, acute respiratory infections, pneumonia, pulmonary tuberculosis, diarrhea, and hepatitis, in the month before the survey. Factors significantly associated with multiple types of infectious diseases were examined using logistic regression. Results The study found that 76.6% of children aged 24 to 59 months in Indonesia had at least one type of infectious disease. The likelihood of developing multiple types of infectious diseases increased in children whose parents did not practice appropriate handwashing with soap and running water [adjusted odds ratio (aOR) = 1.16, p < 0.001], those who received supplemental food (aOR = 1.38, p < 0.001), those with poor nutritional status (aOR = 1.12, p < 0.001), and those living in urban areas (aOR = 1.07, p = 0.045). Conclusion Improving caregivers’ awareness of adequate child healthcare practices, in addition to nutrition-sensitive and specific interventions to improve children’s nutritional status, is required to prevent children from contracting multiple types of infectious diseases.